Geothermally warmed soils reveal persistent increases in the respiratory costs of soil microbes contributing to substantial C losses - Marañón-Jiménez, S; Soong, JL; Leblans, NIW; Sigurdsson, BD; Peñuelas, J; Richter, A; Asensio, D; Fransen, E; Janssens, IA (Biogeochemistry, 2018)
© 2018, Springer International Publishing AG, part of Springer Nature. Increasing temperatures can accelerate soil organic matter decomposition and release large amounts of CO2to the atmosphere, potentially inducing positive warming feedbacks. Alterations to the temperature sensitivity and physiological functioning of soil microorganisms may play a key role in these carbon (C) losses. Geothermally active areas in Iceland provide stable and continuous soil temperature gradients to test this hypothesis, encompassing the full range of warming scenarios projected by the Intergovernmental Panel on Climate Change for the northern region. We took soils from these geothermal sites 7 years after the onset of warming and incubated them at varying temperatures and substrate availability conditions to detect persistent alterations of microbial physiology to long-term warming. Seven years of continuous warming ranging from 1.8 to 15.9 °C triggered a 8.6–58.0% decrease on the C concentrations in the topsoil (0–10 cm) of these sub-arctic silt-loam Andosols. The sensitivity of microbial respiration to temperature (Q10) was not altered. However, soil microbes showed a persistent increase in their microbial metabolic quotients (microbial respiration per unit of microbial biomass) and a subsequent diminished C retention in biomass. After an initial depletion of labile soil C upon soil warming, increasing energy costs of metabolic maintenance and resource acquisition led to a weaker capacity of C stabilization in the microbial biomass of warmer soils. This mechanism contributes to our understanding of the acclimated response of soil respiration to in situ soil warming at the ecosystem level, despite a lack of acclimation at the physiological level. Persistent increases in the respiratory costs of soil microbes in response to warming constitute a fundamental process that should be incorporated into climate change-C cycling models.